1996
DOI: 10.1084/jem.184.3.1173
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of blood mononuclear cell nitric oxide synthase type 2 in rheumatoid arthritis patients.

Abstract: SummaryNitric oxide (NO) is an important inflammatory mediator in nonhuman animal models of rheumatoid arthritis (RA). The purpose of the present study was to determine whether blood mononuclear cells from patients with active RA (as compared to control subjects) have higher levels of NO synthase type 2 (NOS2) and produce more NO in vitro. Leukocytes from 25 RA patients and 20 normal subjects were examined. Arthritis activity was assessed by tender and swollen joint counts, duration of morning stiffness, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
72
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 32 publications
1
72
1
1
Order By: Relevance
“…2,3 Studies in experimental animal models of arthritis have suggested that excessive levels of NO can promote tissue injury and contribute to progression of the disease. 3 Likewise, it has been shown that peripheral blood mononuclear cells (PBMC) from RA patients, have increased NOS2 expression and enhanced formation of NO that correlates with disease activity 4 and similarly, NO has been shown as a key mediator of apoptosis within the RA joints 5 as well as an important regulator of the Th1/Th2 balance in autoinmune diseases. 6 The final piece of evidence comes from the finding that administration of NOS2 inhibitors has provided beneficial effects on animal models of RA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Studies in experimental animal models of arthritis have suggested that excessive levels of NO can promote tissue injury and contribute to progression of the disease. 3 Likewise, it has been shown that peripheral blood mononuclear cells (PBMC) from RA patients, have increased NOS2 expression and enhanced formation of NO that correlates with disease activity 4 and similarly, NO has been shown as a key mediator of apoptosis within the RA joints 5 as well as an important regulator of the Th1/Th2 balance in autoinmune diseases. 6 The final piece of evidence comes from the finding that administration of NOS2 inhibitors has provided beneficial effects on animal models of RA.…”
Section: Introductionmentioning
confidence: 99%
“…9 Tandem repeat variations within the promoter region may affect NOS2 transcription explaining the differences observed in NOS2 expression and NO formation between RA patients and control subjects. 4 With regard to this, variation in the number of CCTTT repeats has been shown to be functionally important in the regulation of NOS2 transcription. 10 The purpose of the present study was to address the possible contribution of the described polymorphism located within the NOS2 promoter region to the susceptibility and/or severity of RA.…”
Section: Introductionmentioning
confidence: 99%
“…NO, as generated in activated macrophages by iNOS, is an important event in host defenses and it modulates the synthesis of prostaglandins, tormboxans and other inflammatory molecules [17]. Despite the beneficial roles of NO in host defense mechanism against tumor cells, viral replication and other factors, and over expression of NO can be harmful to the host, leading to rheumatoid arthritis [22], experimental allergic encephalomyelitis [4] and allograft rejection [27]. Thus, selective inhibition of iNOS can be beneficial to control the production of NO.…”
Section: Introductionmentioning
confidence: 99%
“…In response to various inflammatory stimuli, lung endothelial, alveolar, and airway epithelial cells, as well as activated alveolar macrophages, produce both NO and O 2 Ϫ ⅐ (9, 13). Recent studies implicated NO and ONOO Ϫ in the pathogenesis of many diseases, such as septic shock, arthritis, acute lung injury, and atherosclerosis (19,28,30,33). Reactive oxygen-nitrogen intermediates (RONS) have also been demonstrated to have inhibitory effects on Na ϩ transport across epithelia (1,11,15,20).…”
mentioning
confidence: 99%